2017
DOI: 10.1002/ece3.3105
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational plasticity as an important mechanism affecting response of clonal species to changing climate

Abstract: In spite of the increasing number of studies on the importance of transgenerational plasticity for species response to novel environments, its effects on species ability to respond to climate change are still largely unexplored. We study the importance of transgenerational plasticity for response of a clonal species Festuca rubra. Individuals from four natural populations representing two levels of temperature and two levels of precipitation were cultivated in four growth chambers that simulate the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 80 publications
2
45
2
Order By: Relevance
“…Adaptive parental environmental effects of these treatments have also been reported in other species. For example, parental ‘wounding’ induced resistance against natural herbivory pressure in Mimulus guttatus (Colicchio ). Similarly, parental ‘shading’ is known to enhance the adaptation of Campanula americana to its shaded natural habitats (Galloway and Etterson ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive parental environmental effects of these treatments have also been reported in other species. For example, parental ‘wounding’ induced resistance against natural herbivory pressure in Mimulus guttatus (Colicchio ). Similarly, parental ‘shading’ is known to enhance the adaptation of Campanula americana to its shaded natural habitats (Galloway and Etterson ).…”
Section: Discussionmentioning
confidence: 99%
“…In theory, these effects are advantageous when parental, and offspring environments are correlated (Ezard et al , Leimar and McNamara , Groot et al ), and this is supported by experimental evidence. For instance, offspring of wounded Mimulus guttatus plants showed reduced herbivory damage in two field sites (Colicchio ), and offspring of shaded or non‐shaded Campanulastrum americanum plants showed increased fitness when their light regime matched their parent's environment (Galloway and Etterson ). However, in a meta‐analysis Uller et al (2013) found only weak evidence that offspring perform better on average in environments similar to that of the maternal plant.…”
Section: Introductionmentioning
confidence: 99%
“…We used the term genotype throughout the subsequent text for the plants as we worked with individuals that were genetically differentiated from each other thus representing true independent genotypes (Supplementary material Appendix 1). Details on the plant collection and cultivation are provided in Münzbergová et al (2017). In October 2015, we chose six genotypes per population and planted 12 single ramets per genotype separately into 10 × 10 × 10 cm pots in a greenhouse.…”
Section: Study Systemmentioning
confidence: 99%
“…Based on our previous results Münzbergová et al (2017) and studies of Wilschut et al (2016) and Verhoeven et al (2016) we predicted that 1) demethylation will significantly affect performance of the plants, 2) the effects of demethylation will strongly interact with plant origin and conditions of cultivation, 3) after demethylation, the plant response to conditions of cultivation will be less affected by origin of the population because epigenetic differentiation is expected to be an important driver of phenotypic between population differentiation, 4) effects of demethylation will differ between genotypes, 5) the differences between genotypes will depend on their genetic relatedness and 6) epigenetic differentiation of the populations will have an adaptive value, i.e. naturally methylated plants will perform better at their home environment than foreign plants, while demethylated plants will not show such a pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation